Molecular Detection and Genotyping of Chlamydia psittaci in Birds in Buenos Aires City, Argentina - Madariaga, María Julia (2024)
Chlamydia psittaci is a bacterium that infects birds and mammals and is one of the main zoonotic pathogens transmitted by birds. It is the causal agent of avian chlamydiosis and psittacosis in humans and it is globally distributed. In Argentina, there has been limited research on this pathogen. The aim of this study was to detect and genotype Chlamydia psittaci using molecular techniques in birds living in Buenos Aires City, Argentina, during the period 2012–2015. A descriptive study was carried out with a total of 983 bird samples submitted for diagnosis of avian chlamydiosis. The frequency of Chlamydia psittaci was 12.54% and 7.89% in psittacine birds and pigeons, respectively. Of those samples, 83 were positive and 44 could be sequenced. The genotypes found were A, B, and E. Despite the high levels of host specificity, we found six psittacids with genotype B and one pigeon with genotype A, reflecting the affiliative interaction between these two groups of birds. This study represents the first survey reporting the presence of Chlamydia psittaci in birds in Buenos Aires City, which will contribute to the knowledge of the ecoepidemiology of this bacterium in the largest and most populous city in Argentina.